2011
DOI: 10.1080/1475939x.2011.610932
|View full text |Cite
|
Sign up to set email alerts
|

Chasing dreams and recognising realities: teachers’ responses to ICT

Abstract: The teaching profession's response to the inexorable march of new technology into education has been a focus of research for some 30 years. Linked with the impact of ICT on measurable performance outcomes, teacher attitudes to technology and the impact on pedagogic practice have been central to that research, a research that has often seen teachers as a barrier, not a force for change. The current article brings together findings from a decade of studies that have explored the ways in which teaching staff have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 24 publications
1
62
0
12
Order By: Relevance
“…Our findings are related more generally to those of Christensen and Knezek (2008), Yuen and Ma (2002), Mumtaz (2000), Sipilä (2013), Howard (2013), Loveless (2011) and Underwood and Dillon (2011), which show that it is often a combination of demographic, personal and professional characteristics that affect teachers' use of ICT in teaching and digital literacy. Our findings complement Ferrari's (2012) analysis of the framework of digital competence in practice.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our findings are related more generally to those of Christensen and Knezek (2008), Yuen and Ma (2002), Mumtaz (2000), Sipilä (2013), Howard (2013), Loveless (2011) and Underwood and Dillon (2011), which show that it is often a combination of demographic, personal and professional characteristics that affect teachers' use of ICT in teaching and digital literacy. Our findings complement Ferrari's (2012) analysis of the framework of digital competence in practice.…”
Section: Discussionsupporting
confidence: 56%
“…Cox et al (1999) and Cuban et al (2001) found the same tendencies as well as challenges related to the school management level. Recent studies conducted by Sipilä (2013), Howard (2013), Loveless (2011) and Underwood and Dillon (2011) show that teachers' use of ICT in teaching can represent a number of new opportunities as well as a number of challenges (which are also related to a lack of digital competence 3 ). One assumption that is shared by several different positions and studies dealing with digital literacy and ICT in teaching is that teachers' digital competence is more complex than digital literacy in other occupations and among average citizens.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Pourtant, malgré l'importance que revêtent les TIC sur les plans socioprofessionnel et éducatif, on note que leur usage en contexte d'apprentissage demeure toujours un immense défi (Underwood et Dillon, 2011) ou que les usages pédagogiques sont trop limités (BECTA, 2007;DEPP, 2010;Thibert, 2012). Un rapport du CEFRIO (2011) faisait ainsi remarquer que « les TIC sont omniprésentes dans la vie des élèves et des étudiants […] ceux-ci s'en servent continuellement pour se divertir, pour communiquer avec leurs amis ou pour faire leurs devoirs.…”
unclassified
“…The teacher by using an interactive CD which contains historical facts, still and moving images, questions, feedbacks and digital maps, and employing more student centered teaching approach such as group work and inquiry based teaching, appears to make a small contribution to pupils' achievement level. It is not straightforward process to make pupils achieve better trough ICT integration (Underwood and Dillon, 2011;Acun, 2014). Therefore, it is suggested hereby that teachers training programs of ICT integration has to subject oriented and carried out in a workshop manner over a long period of time.…”
Section: Discussionmentioning
confidence: 99%